Entrepreneurial attitude of tertiary students in Singapore - Ang, Kaisi (2008)
To conduct a study on the entrepreneurial attitude of teriary students in Singpore, and its implications. The purpose is to evaluate if entrepreneurs are born or made; if made, do factors like the institution and family background play a part.